2021
DOI: 10.1177/14680173211009188
|View full text |Cite
|
Sign up to set email alerts
|

Service user violence against social workers in Italy: Prevalence and characteristics of the phenomenon

Abstract: Summary Client violence in social services is perceived as constantly increasing in Italy, raising deep concern. This article presents the results of the first online survey on the phenomenon. Involving 20,112 social workers, the aim was to determine the prevalence and forms of client violence towards social workers and to identify key factors associated with such events. Findings The results suggest that the vast majority of Italian social workers experience client violence during their careers. Verbal aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In relation to experiences with violence and coping strategies, the study confirmed that the context and causes of client violence among social workers lead the workers to adopt passive -and mainly individualized -coping strategies. As previously shown (Sicora et al, 2021;Zelnick et al, 2013), professionals in Reconnecting assume violence to be a part of their work. An important result in this case is that supervisors also normalize client violence through collective meetings.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In relation to experiences with violence and coping strategies, the study confirmed that the context and causes of client violence among social workers lead the workers to adopt passive -and mainly individualized -coping strategies. As previously shown (Sicora et al, 2021;Zelnick et al, 2013), professionals in Reconnecting assume violence to be a part of their work. An important result in this case is that supervisors also normalize client violence through collective meetings.…”
Section: Discussionmentioning
confidence: 80%
“…In this way, Ringstad (2005) reports that 60 percent of the participants were victims of client violence, and similar to the Australian study, verbal aggression was the most commonly reported form of client violence ( Jayaratne et al, 2004 ). In Italy, a national study that centered on more than 20,000 social workers ( Sicora et al, 2021 ) found that most professionals experienced client violence. In addition, the study confirmed that verbal aggression and threats were the most common forms of client violence, and to be male, young, and working alone were most at-risk factors of experiencing client violence, as previous studies on social workers had also noted ( Balloch et al, 1998 ; Choi and Choi, 2015 ; Jayaratne et al, 2004 ; Littlechild et al, 2016 ).…”
Section: Client Violence Against Social Workers In Social and Health ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The word violence is the most used as a keyword or word in the title of an article. It is customary to combine it with the client concept, as a causal agent of violence towards the professional (Sicora et al, 2021;Sousa et al, 2014;Virkki, 2008).…”
mentioning
confidence: 99%